Oxidative Stress in Spinocerebellar Ataxia Type 7 Is Associated with Disease Severity - Torres-Ramos, Y.; Montoya-Estrada, A.; Cisneros, B.; Tercero-Pérez, K.; León-Reyes, G.; Leyva-García, N.; Hernández-Hernández, Oscar; Magaña, Jonathan J. (Cerebellum (London, England), 2018)
Spinocerebellar ataxia type 7 is a neurodegenerative inherited disease caused by a CAG expansion in the coding region of the ATXN7 gene, which results in the synthesis of polyglutamine-containing ataxin-7. Expression of mutant ataxin-7 disturbs different cell processes, including transcriptional regulation, protein conformation and clearance, autophagy, and glutamate transport; however, mechanisms underlying neurodegeneration in SCA7 are still unknown. Implication of oxidative stress in the pathogenesis of various neurodegenerative diseases, including polyglutamine disorders, has recently emerged. We perform a cross-sectional study to determine for the first time pheripheral levels of different oxidative stress markers in 29 SCA7 patients and 28 age- and sex-matched healthy subjects. Patients with SCA7 exhibit oxidative damage to lipids (high levels of lipid hydroperoxides and malondialdehyde) and proteins (elevated levels of advanced oxidation protein products and protein carbonyls). Furthermore, SCA7 patients showed enhanced activity of various anti-oxidant enzymes (glutathione reductase, glutathione peroxidase, and paraoxonase) as well as increased total anti-oxidant capacity, which suggest that activation of the antioxidant defense system might occur to counteract oxidant damage. Strikingly, we found positive correlation between some altered oxidative stress markers and disease severity, as determined by different clinical scales, with early-onset patients showing a more severe disturbance of the redox system than adult-onset patients. In summay, our results suggest that oxidative stress might contribute to SCA7 pathogenesis. Furthermore, oxidative stress biomarkers that were found relevant to SCA7 in this study could be useful to follow disease progression and monitor therapeutic intervention.